2014
DOI: 10.1007/s00380-014-0578-4
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary feasibility study of simultaneous dual-isotope imaging with a solid-state dedicated cardiac camera for evaluating myocardial perfusion and fatty acid metabolism

Abstract: Simultaneous dual-isotope SPECT imaging with 201Tl and (123)I-β-methyl-p-iodophenylpentadecanoic acid (BMIPP) is used to study the perfusion-metabolism mismatch. It predicts post-ischemic functional recovery by detecting stunned myocardium. On the other hand, (99m)Tc-MIBI is another radioisotope widely used in myocardial perfusion imaging because of its better image quality and lower radiation exposure than 201Tl. However, since the photopeak energies of (99m)Tc and (123)I are very similar, crosstalk hampers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The feasibility of simultaneous imaging of inflammation with 111 In-labeled white cells and myocardial perfusion with technetium (99mTc) sestamibi was demonstrated in the phantom and in 34 patients [42]. Simultaneous imaging of fatty metabolism with 123I-β-methyliodophenylpentadecanoic acid and perfusion with technetium (99mTc) sestamibi has been shown in 30 patients [43]. An 123I-metaio dobenzylguanidine/201Tl imaging protocol has been proposed for evaluation of trigger zones after revascularization [44].…”
Section: Simultaneous Dual-isotope Imagingmentioning
confidence: 99%
“…The feasibility of simultaneous imaging of inflammation with 111 In-labeled white cells and myocardial perfusion with technetium (99mTc) sestamibi was demonstrated in the phantom and in 34 patients [42]. Simultaneous imaging of fatty metabolism with 123I-β-methyliodophenylpentadecanoic acid and perfusion with technetium (99mTc) sestamibi has been shown in 30 patients [43]. An 123I-metaio dobenzylguanidine/201Tl imaging protocol has been proposed for evaluation of trigger zones after revascularization [44].…”
Section: Simultaneous Dual-isotope Imagingmentioning
confidence: 99%
“…In simultaneous dual-radionuclide imaging, even if the energy resolution of the CdTe detectors is very good, down-scatter is unavoidable. Furthermore, scatter within the crystals, k-escape, and incomplete charge collection can cause a considerable fraction of the primary gamma rays to be measured as lower energy events [ 4 8 ]. An iterative deconvolution-based scatter and crosstalk correction method for simultaneous dual-radionuclide imaging and a solid-state detector SPECT system have been developed [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The method improves the contrast in simultaneous Tc-99m and Tl-201 imaging using CdZnTe-based SPECT. The feasibility of using this method for simultaneous Tc-99m and I-123 cardiac imaging has been investigated [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The scanning of multi-radionuclide pharmaceuticals will enable various kinds of functional images to be obtained without position error or time difference. The recent development of several cardiac SPECT systems that use solid-state detectors with a fine energy resolution [3][4][5] has led to simultaneous multi-radionuclide imaging recapturing the spotlight. A number of simultaneous multiradionuclide imaging studies have been reported, especially for myocardial perfusion diagnosis [4,5].…”
Section: Introductionmentioning
confidence: 99%